Togunggak : Traditional Music of Kadazandusun - Ezra Alfandy, M Duin; Sinin, Hamdan; Khairul Anwar, Mohamad Said; Kuryati, Kipli; Aaliyawani Ezzerin, Sinin; Ahmad Faudzi, Musib (North Carolina State University, 2025)
The togunggak is a traditional musical instrument made of bamboo. This work observed the unique sound characteristics to define the notes using Fast Fourier Transform (FFT) via a picoscope. The sound characteristics are represented by the dominant frequency with the corresponding intensity. The note of the biggest (tog. 6) to the smallest (tog. 1) bamboo tube is recorded as from G3 to G4. This work reveals that tog. 2 to tog. 5 for togunggak A produce the notes E4, D4, B3, and A3, which is not similar to togunggak B, i.e., E4, D4, C4, Bb3. All bamboo tubes produced fundamental frequency with the presence of two lower partials at 100 Hz and 200 Hz and weaker overtones (except tog. 6) in their frequency spectrum. Using symbol S for semitone dan T for tone (i.e. 2 semitone), the note interval of the tog. 6 to tog. 1 can be presented as TT2TT2T i.e., the G3, A3, B3, D4, E4, G4 note interval are presented by G3-A3 as T, A3-B3 as T, B3-D4 as 2T, D4-E4 as T and E4-G4 as 2T. The time frequency analysis (TFA) displays all the spectrograms with distinct prominent fundamental frequency peak.